Lipid-lowering therapy after acute coronary syndromes in Europe: can we do better?. (3rd May 2023) - Tsaban, G; Vidal Perez, R; Krychtiuk, K K; Ahrens, I; Halvorsen, S; Hassager, C; Huber, K; Schiele, F; Sionis, A; Claeys, M J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Recent guidelines on acute coronary syndromes (ACS) recommend initiating lipid-lowering therapy (LLT) as soon as possible in order to obtain >50% LDL-cholesterol reduction with a low-density-lipoprotein-cholesterol (LDL-c) <1.4 mmol/L. Aim: To define the current LLT policy in Europe after an ACS and to assess whether in hospital initiation of combination therapy of high potency (HP) statin with or without ezetimibe improves the adherence rate to target LDL-c levels as compared to a step-by-step LLT approach. Methods and results: Data on LLT and lipid levels during and up to one year after hospitalisation were gathered retrospectively for 286 ACS patients who were admitted in 28 hospitals (70% academic) across 16 European countries between the years 2021 and 2022. Patients (median age 61 years, 75.9% men) were mostly admitted in dedicated cardiology departments/intensive cardiac care units (96.8%). A total 59% had ST-elevation myocardial infarction and 88% were treated with percutaneous coronary intervention. At baseline 69.9% of the patients had dyslipidaemia, 35 (14.6%) were on HP statin, 5 (3.9%) were on ezetimibe, and 6 (2.2%) were on HP statin/ezetimibe combination therapy. The median LDL-c on admission was 3.27 [interquartile range (IQR): 2.4-4.1] mmol/L. HP statin only was the predominant LLT during hospitalisation (62%) and was primarily initiated within 24h from admission (figure). During hospitalization, HP statin/ezetimibe combination therapy was administered in 24.0% of the cases. Combination therapy in hospital was given more frequently in high income countries (n=8) as compared to middle income countries (34.0% vs 10.8%, p<0.001). After one year, LLT up titration to combination therapy with ezetimibe or with PCSK9 inhibition was observed among 40 patients (14%, to a total of 37.4%) and 3 patients (1.6%), respectively. At follow-up, median LDL-c level was 1.6 (IQR 1.3-2.0) mmol/L and the median relative LDL-c reduction was 45.4% (IQR 27.2-64.0). Adherence to target LDL-c with > 50% reduction was achieved in 17.8% of the total population, in 22.4% of the high-income countries and in 12.3% of the middle-income countries (p=0.04). Patients treated with combination therapy at discharge had a higher relative LDL-c reduction than those with HP statin therapy only at discharge (median 52.5% vs 43.8%, p=0.007) and had a numerically higher target lipid status (23.9% vs 17.2%, p=0.24) Conclusions: Despite high rates of high intensity LLT during hospitalisation, target LDL-c with > 50% LDL reduction was achieved only in 17.8%. Greater, yet insufficient, LDL-c reduction was observed when combination therapy of high dose statin with ezetimibe was initiated during the index hospitalisation.